The IGF/IGFBP system in CNS malignancy. Issue 4 (1st August 2001) - Zumkeller, W; Westphal, M
Abstract : The insulin-like growth factor (IGF) system includes IGF-I and IGF-II, the type I and type II IGF receptors, and specific IGF binding proteins (IGFBP-1 to IGFBP-6). These factors regulate both normal and malignant brain growth. Enhanced expression of IGF-I and IGF-II mRNA transcripts has been demonstrated in gliomas, meniningiomas, and other tumours. Abnormal imprinting of IGF-II occurs in gliomas, medulloblastomas, and meningiomas. Both types of IGF receptor are expressed in gliomas and, in particular, the type I IGF receptor appears to be upregulated in malignant brain tissue. Antisense IGF-I receptor mRNA induces an antitumour response, resulting in complete brain tumour regression. Clinical trials for the treatment of brain tumours in humans based on a gene transfer protocol using IGF-I receptor antisense are under way. All six IGFBPs are expressed to a variable extent in brain tumours. High concentrations of IGFBP-2 are found in cerebrospinal fluid from patients with malignant central nervous system tumours; therefore, IGFBP-2 might be a useful marker for these tumours. IGFBP-4 appears to be a negative regulator of tumour proliferation. Both in vitro and in vivo experiments suggest that the IGF system represents an important target for the treatment of malignant central nervous system tumours and the ongoing trials should provide valuable information for future therapeutic approaches.